The Impact of Tick-Borne Diseases on the Bone - Imran Farooq; Tara J. Moriarty (Microorganisms, 2021)
Tick-borne infectious diseases can affect many tissues and organs including bone, one of the most multifunctional structures in the human body. There is a scarcity of data regarding the impact of tick-borne pathogens on bone. The aim of this review was to survey existing research literature on this topic. The search was performed using PubMed and Google Scholar search engines. From our search, we were able to find evidence of eight tick-borne diseases (Anaplasmosis, Ehrlichiosis, Babesiosis, Lyme disease, Bourbon virus disease, Colorado tick fever disease, Tick-borne encephalitis, and Crimean–Congo hemorrhagic fever) affecting the bone. Pathological bone effects most commonly associated with tick-borne infections were disruption of bone marrow function and bone loss. Most research to date on the effects of tick-borne pathogen infections on bone has been quite preliminary. Further investigation of this topic is warranted.